Odpowiedzi

2010-01-11T18:31:09+01:00
2010-01-11T18:53:07+01:00
A)
-y-y=6
-2y=6/-2
y=-3
b)
y=x+3
2x+x+3=9
y=x+3
3x=12/3
x=4
y=x+3
c)
x-4x=15
y=4x
-3x=15/-3
x=5
y=4x
d)
y=-2(y+7)-1
x=y+7
y=-2y+7-1
x=y+7
3y=6/3
x=y+7
y=2
e)
-3x=2(1-x)
y=1-x
-3x=2-x
y=1-x
-2x=2/-2
y=1-x
x=1
f)
5(4y-1)+6y=8
x=4y-1
20y-1+6y=8+1
x=4y-1
26y=9/26
x=4y-1
y=???



Najlepsza Odpowiedź!
2010-01-11T18:58:38+01:00
A ) x=-y
x-y=6

x=-y
-y-y=6

x=-y
-2y=6 / : -2

x=-y
y= -3

x= -3
y= -3

B) y=x+3
2x+y=9

y=x+3
2x+x+3 = 9

y=x+3
3x= 6 /:3

y=x+3
x = 2

y=2+3
x=2

y=5
x=2
C) x-y=15
y=4x

x-4x=15
y=4x

-3x = 15 /: (-3)
y=4x

x=-5
y=4*(-5)

x=-5
y= -20

D) y=-2x-1
x=y+7

y=-2x - 1
x=-2x-1 + 7

y=-2x-1
3x=6 /: 3

y=-2x-1
x=2

y=-2*2-1
x=2

y=3
x=2

e) -3x=2y
y=1-x

-3x=2(1-x)
y=1-x

-3x= 2 -2x
y=1-x

x=-2
y=1+2

x=-2
y=3

F) 5x+6y=8
x=4y-1

5(4y-1) + 6y = 8
x=4y-1

20y - 5 + 6y = 8
x=4y-1

26y = 13 / : 26
x=4y-1

y=13/26 = ½
x=4 * ½ - 1 = 2 -1 = 1
1 5 1